A comparative study on the dry sliding wear behaviour of nitrocarburised, gas nitrided, fluidised-bed nitrided, and plasma nitrided plastic mould steel. (2016) - Boztepe, E.; Alves, A.C.; Ramalho, A.; Ariza, E.; Rocha, L.A.; Cansever, N.; Toptan, F.
Plastic injection moulds suffer wear due to the relative movements of the mould parts and the polymeric material flow which is often reinforced by hard abrasive fibres or whiskers. Several studies were performed on the wear behaviour of diverse nitrided surfaces; however, comparative studies are needed. The present study aims to compare the dry sliding wear behaviour of nitrocarburised, gas-nitrided, fluidised-bed nitrided, and plasma-nitrided Impax Supreme (equivalent to AISI P20) pre-hardened plastic mould steel. The wear tests were performed against AISI 4140 pins under 100 N normal loads, with the total stroke length of 10 mm, the frequency of 1.5 Hz, and the total sliding distance of 400 m. After tests, worn surfaces and wear debris were microstructurally and chemically characterised and the wear rates were calculated. Results suggested that all samples presented mainly combination of adhesive and abrasive wear during the run-in period of sliding (severe wear), and mainly oxidative wear during the steady-state of (mild wear). Although no significant difference was observed between the treated samples, plasma-nitrided samples presented the lowest wear rate as mean values.